2018
DOI: 10.14295/idonline.v12i41.1254
|View full text |Cite
|
Sign up to set email alerts
|

Correlação entre Leishmaniose Visceral e Indicadores Socioeconômicos

Abstract: Resumo: O objetivo do estudo foi descrever a distribuição espacial e evolução da leishmaniose visceral (LV) no período de 1986 a 2017 e sua correlação com indicadores socioeconômicos no estado do Ceará, com base nos boletins emitidos pela Secretaria Estadual de Saúde do Ceará e documentos do Ministério da Saúde e Atlas Brasil. Os dados foram analisados através do programa Bioestat 5.0. Constatou-se que a LV encontra-se distribuída em 95% do território cearense, com taxa de incidência de 1,9 a 9,1/100.000 hab e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 1 publication
1
7
0
Order By: Relevance
“…Studies have demonstrated socioeconomic factors related to VL in different locations , Costa et al, 2005 through different mechanisms. The included studies pointed out the high incidence of VL associated with the worst living conditions of the populations and the lowest urban structure corroborating with the study by Araújo et al (2018). Such factors are also responsible for the expansion of the disease in endemic regions (da .…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Studies have demonstrated socioeconomic factors related to VL in different locations , Costa et al, 2005 through different mechanisms. The included studies pointed out the high incidence of VL associated with the worst living conditions of the populations and the lowest urban structure corroborating with the study by Araújo et al (2018). Such factors are also responsible for the expansion of the disease in endemic regions (da .…”
Section: Discussionsupporting
confidence: 80%
“…The lowest per capita income and the lowest human development index showed a positive correlation with the average number of cases of VL (Araújo et al ., 2018). The annual incidence rates of VL correlated with the average income and illiteracy (Cerbino-Neto et al ., 2009).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Araújo et al (2018), human VL transmission was found in 95% of Ceará municipalities from 2014 to 2016, in which 14% of them were classified as areas with intense risk of transmission; several of these municipalities also made up the clusters identified in this research (Ceará, 2019). This result was corroborated by findings reported in previous studies.…”
Section: F I G U R Ementioning
confidence: 62%
“…It is noteworthy that the increase in temperature also increases the density of adult vectors and, in turn, the contact between vector and hosts and, consequently, spread of the disease (Araújo et al, 2018).…”
Section: F I G U R Ementioning
confidence: 99%